Performa Kebijakan Kampus Merdeka pada Program Magang dan Studi Independen Bersertifikat - An Nisaa' Budi Sulistyaningrum; Nurulita Artanti Nirwana; Dhiya Ratri Januar; Nela Najwa Hilalia (Jurnal Multidisiplin Madani, 2022)
Education is a communication process that involves transforming knowledge, values, and skills both inside, and outside the school. Education is one of the compulsory guarantees of education and is provided by the central government to the local government. Ministries of Education, Culture, Research, and Technology established a free learning policy (MBKM), and one of the programs on MSIB policy is a certified internship and independent study (MSIB). This program provides an opportunity for students to have off-campus learning experiences for a semester or two. The study uses qualitative methods, and the data analysis techniques used in the study are the methods for library research. In this case, an alternative policy would be a policy recommendation with an alternative policy recommendation of  MSIB programs capable of producing both hard skills and soft skills students acquired from followed activities and implemented programs running optimally.